The impact of corporate violations on charitable donation behavior - Zhu, Qing; Yuan, Fangying; Wang, Chuming; Luan, Dongqing; Wang, Hong (Frontiers in Psychology, 2023)
The motivation behind corporate charitable donations has been the focus of several academic debates. From a corporate violation perspective, this paper employs Chinese A-share non-financial enterprises from 2011 to 2020 as a sample to empirically test the relationship between corporate violations and corporate charitable donation behavior. Moreover, the heterogeneity effects of enterprise ownership type, analyst attention, and information transparency are further investigated. Consequently, the following conclusions are presented. First, corporate violations are significantly positively correlated with the level of corporate charitable donations. Second, among the companies with high analyst attention, high information transparency, or non-state-owned nature, the positive impact of enterprise violations on charitable donations is greater. These findings suggest that charitable giving may be used by some businesses as a bad tool to conceal their irregularities. This article enriches the related research in the field of corporate charitable donation motivation. It has practical significance vis-à-vis attaining a comprehensive understanding of corporate charitable donation behavior, as well as the identification and suppression of “hypocritical” corporate charitable donation behavior.